Temple Compound, Golden Gate International Exposition, San Francisco (H.S. Crocker Co., Inc.)
The Temple Compound as viewed across one of the Lakes of the Nations at San Francisco's World's Fair on Treasure Island, showing the Towers of the East, golden bas-reliefs, the Court of Flowers, the Arch of Triumph, and the Tower of the Sun.